"Aú, água fresca, água fresquinha": a Humanistic Analysis about the Figure of the Galician Water-carriers in Lisbon - Pérez Coelho, Ana Claudia (Madrygal. Revista de Estudios Gallegos, 2018)
Galicians had been since antique Rome a people worthy of admiration known for their strength, determination and resistance. These qualities did not change as immigrants in the city of Lisbon. They represented a big number as immigrants in Lisbon, even thousands, who dedicated particularly to menials and hard works among which it stands the water-carrier, a person that carried and sold water in the street. Furthermore, in Lisbon, be a water-carrier meant to extinguish difficult fires of houses and be the particular and faithful courier for any matter, even love affairs. This study aims to show, from a humanistic perspective, the figure of the Galician water-carriers in Lisbon. Mostly it focuses on the economic, social and cultural role that it represented for the city and its decadence as an immigrant group that time ago dominated the water supply of the capital, finally achieving to stay in the memory of the city and be part of the Portuguese literature.
Keywords: Galician; Immigrant; Lisbon; Spring; Water-carrier.